The Foresight of Blockchain Technology in E-commerce in Kuala Lumpur and Selangor, Malaysia - Sabrina Goh Ming Jie; Muhammad Ammar Shafi (Research in Management of Technology and Business, 2022)
In the technology era, implementing blockchain technology in the industries are getting familiar and emphasized as the technology offers maximum convenience and security. The adoption of blockchain technology in e-commerce is still under observation along with its advantages and disadvantages. Several studies discussed blockchain technology, however, there is still very little research on the implementation of blockchain technology in the e-commerce industry. Hence, this study aims to investigate the key drivers and explore the future trends of blockchain technology in e-commerce in Kuala Lumpur and Selangor. The research respondents included the developers and users of blockchain technology and users of e-commerce. A mixed-method approach was used to collect both primary and secondary data. The STEEPV analysis is used to determine the issues and drivers related to implementing blockchain technology, while the SPSS software analyzes the data collected. A total of 88 out of 100 respondents participated in the survey. The survey response rate of the research was 88%. The outcomes of the study concluded the two top drivers based on their importance, impact, and uncertainty level, the di are gitalization and awareness of adopting blockchain technology. Then, the future trends of four scenarios were formulated with scenario building. This study may benefit future researchers, e-commerce industries, and users of blockchain technology as it provides various possibilities for enhancing the e-commerce processes.